Os desdobramentos das reformas de educação profissional e tecnológica promovidas pelos governos Fernando Henrique Cardoso e Lula da Silva no Instituto Federal do Ceará, campus Juazeiro do Norte - Trigueiro, Nilene Matos (2014)
This thesis proposes to examine the Federal Institute of Technological Education of Ceará (IFCE) campus Juazeiro, in advance of the neoliberal policies of vocational and technological education, undertaken by the governments of Fernando Henrique Cardoso and Lula da Silva. The research seeks to read between the lines, discussing the economic, political and ideological interests in the constitution of legislation related to vocational and technical education, developed by the governments of Fernando Henrique Cardoso and Lula da Silva, with emphasis on Decree No. 2,208 / 1997 recorded the first and Decree No. 5,154 / 2004 and Law No. 11,892 / 2008, promulgated by the second. To understand reality, the job will leave the dialectical method, believing that this allows the construction and reflection of reality in its historical entirety. Given the above, the research question that is intended to clarify is this: as the definitions contained in vocational and technical education reforms implemented since the second half of the 90s of XX century, were being implemented, or not, in IFCE campus Juazeiro? This presents the hypothesis that the policies of professional and technological education, developed in recent decades, the Brazilian government pledged more with the market and international agencies than with the needs and interests of workers in the country. From a methodological standpoint, we opted for a qualitative study. The methodological approach was selected to bibliographic and documentary research, since this gives the investigator the opportunity to gather a lot of information pertaining to its object through the use of laws, procedures and school conditions etc. The search can also be defined as a case study by allowing the deepening of a certain reality. In this case, the reality to be known is the IFCE campus Juazeiro, in order to get to know the impact of policies on vocational and technical education, enacted by governments Fernando Henrique Cardoso and Lula da Silva, the reality in question. A survey conducted in IFCE campus Juazeiro, made it clear that reform in vocational and technical education, promoted by Fernando Henrique Cardoso, settled himself ideologically and financially to the capital accumulation process, in view of consolidating the state minimum in that economic regulation should be undertaken by market forces, and the state should provide the minimum necessary services, such as education, safety, health etc. Regarding reform in vocational and technical education held by the Lula da Silva government, could be seen that, despite some advances in education, promoted by his government in recent decades, causing qualitative changes from the previous government, these advances still were not able to counter the neoliberal conceptions of education, nor were sufficient to promote a comprehensive education in the perspective of emancipation of the working class.